Static analysis and simplified design of suspension bridges having various rigidity of cables - Grigorjeva, Tatjana; Juozapaitis, Algirdas; Kamaitis, Zenonas (Journal of Civil Engineering and Management, 2010)
Increased deformability can be considered as the basic disadvantage of suspension bridges. One of the ways to increase the rigidity of a suspension bridge is to transfer a part of stiffening girder rigidity to a suspension main cable. To give the suspension bridge more stable appearance, the authors propose to use the cables of varying bending stiffness. The main cables can be made of standard section shapes or have a composite section. The object of this work was to study a method for analyzing and determining the internal forces in the main cables and stiffening girder under static loading to provide recommendations for designing suspension bridges with stiffened cables. Simple formulas are presented for determining displacements, internal forces and stresses in the main cable and stiffening girder. Finite element modeling was performed. The final part of the paper discusses design procedures for such suspension systems. An example of a pedestrian suspension bridge is appended.